Empowerment and Participatory Approaches to Urban Health: The E-City Programme - Lissandrello, Enza; Zepf, Marcus (AESOP, 2024)
This paper explores the importance of urban health in contemporary urban planning. It aims to address the question on how planners can actively contribute to knowledge and practices related to urban health, promoting equality and equity in future cities through empowerment and participation. The study analyses the strategies and initial steps of the method used by E-city, a long-term university program at the University Paris-Est Creteil since 2020. Focusing on intersectionality dynamics in planning and urban health from interviews with project leaders and professionals, survey data, and participation observation, valuable lessons from the E-City program aim to inspire a new generation of planners committed to intersectional approaches to urban health planning. Keywords: intersectionality, pro-equity, urban justice, uncertainty experimentation
Game changer? Planning for just and sustainable urban regions, Paris, 8-12th July 2024